2008
DOI: 10.1103/physrevlett.101.113904
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fiber Systems Are Convectively Unstable

Abstract: We theoretically and experimentally evidence that fiber systems are convective systems since their nonlocal inherent properties, such as the dispersion and Raman effects, break the reflection symmetry. Theoretical analysis and numerical simulations carried out for a fiber ring cavity demonstrate that the third-order dispersion term leads to the appearance of convective and absolute instabilities. Their signature is an asymmetry in the output power spectrum. Using this criterion, experimental evidence of convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 22 publications
(21 reference statements)
3
36
0
1
Order By: Relevance
“…Since, in a realistic system (here an optical fiber), the perturbations can be either extended (CW) or localized, their spatio-temporal evolution cannot be described in the framework of the classical linear stability analysis based on the normal-mode theory (plane waves). More precisely, this analysis is insufficient as it stands [15,16] to account for propagating instabilities induced by time reversal symmetry terms such as the third-order derivative in Eq. (1).…”
Section: Impact Of Third-order Dispersion β 3 On the Dynamicsmentioning
confidence: 98%
“…Since, in a realistic system (here an optical fiber), the perturbations can be either extended (CW) or localized, their spatio-temporal evolution cannot be described in the framework of the classical linear stability analysis based on the normal-mode theory (plane waves). More precisely, this analysis is insufficient as it stands [15,16] to account for propagating instabilities induced by time reversal symmetry terms such as the third-order derivative in Eq. (1).…”
Section: Impact Of Third-order Dispersion β 3 On the Dynamicsmentioning
confidence: 98%
“…In particular, third-order dispersion (TOD) generates the emission of dispersive waves that can lead to the suppression of dynamical regimes such as oscillations and chaos [26,27]. As TOD also breaks reversibility, solitons move with a constant velocity [26][27][28][29][30]. While recent work has numerically shown that TOD induces similar dispersive waves in dark solitons in both normal and anomalous dispersion regions [31], a complete understanding of the influence of TOD on the dynamics and bifurcation structure of dark pulse Kerr frequency combs is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…If the dispersion cannot be considered to be a constant over the spectrum, the TOD term must be taken into account [21][22][23][24][25][26][27][28]. This higher-order term strongly modifies the dynamics of nonlinear systems by making them convectively unstable [21].…”
Section: Introductionmentioning
confidence: 99%
“…If the dispersion cannot be considered to be a constant over the spectrum, the TOD term must be taken into account [21][22][23][24][25][26][27][28]. This higher-order term strongly modifies the dynamics of nonlinear systems by making them convectively unstable [21]. In optical fibers, it leads to the nonlinear symmetry breaking of parametric processes [22][23][24]28], to the generation of Cherenkov radiations (CRs) by solitons [29], which are one of the key elements of supercontinuum generation [30,31], and, in extreme cases, to turbulent dynamics [32,33].…”
Section: Introductionmentioning
confidence: 99%